Strongyle Infection and Gut Microbiota: Profiling of Resistant and Susceptible Horses Over a Grazing Season - Clark, Allison; Sallé, Guillaume; Ballan, Valentine; Reigner, Fabrice; Meynadier, Annabelle; Cortet, Jacques; Koch, Christine; Riou, Mickaël; Blanchard, Alexandra; Mach, Núria (Frontiers in Physiology, 2018)
Gastrointestinal strongyles are a major threat to horses' health and welfare. Given that strongyles inhabit the same niche as the gut microbiota, they may interact with each other. These beneficial or detrimental interactions are unknown in horses and could partly explain contrasted susceptibility to infection between individuals. To address these questions, an experimental pasture trial with 20 worm-free female Welsh ponies (10 susceptible (S) and 10 resistant (R) to parasite infection) was implemented for five months. Fecal egg counts (FEC), hematological and biochemical data, body weight and gut microbiological composition were studied in each individual after 0, 24, 43, 92 and 132 grazing days. R and S ponies displayed divergent immunological profiles and slight differences in microbiological composition under worm-free conditions. After exposure to natural infection, the predicted R ponies exhibited lower FEC after 92 and 132 grazing days, and maintained higher levels of circulating monocytes and eosinophils, while lymphocytosis persisted in S ponies. Although the overall gut microbiota diversity and structure remained similar during the parasite infection between the two groups, S ponies exhibited a reduction of bacteria such as Ruminococcus, Clostridium XIVa and members of the Lachnospiraceae family, which may have promoted a disruption of mucosal homeostasis at day 92. In line with this hypothesis, an increase in pathobionts such as Pseudomonas and Campylobacter together with changes in several predicted immunological pathways, including pathogen sensing, lipid metabolism, and activation of signal transduction that are critical for the regulation of immune system and energy homeostasis were observed in S relative to R ponies. Moreover, S ponies displayed an increase in protozoan concentrations at day 92, suggesting that strongyles and protozoa may contribute to each other’s success in the equine intestines. It could also be that S individuals favor the increase of these carbohydrate-degrading microorganisms to enhance the supply of nutrients needed to fight strongyle infection. Overall, this study provides a foundation to better understand the mechanisms that underpin the relationship between equines and natural strongyle infection. The profiling of horse immune response and gut microbiota should contribute to the development of novel biomarkers for strongyle infection.